2019
DOI: 10.1101/555912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Left-handedness is associated with greater fighting success in humans

Abstract: 14Left-handedness is a costly, sexually dimorphic trait found in all human populations. How the 15 handedness polymorphism is maintained is unclear. The fighting hypothesis argues that left-16 handed men have a negative frequency-dependent advantage in fighting giving them a selective 17 advantage. In support of this, many studies have found that left-handed men are overrepresented 18 in combat sports, but studies typically find no difference in fighting success between left and right-19 handed fighters. We st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…These studies laid the foundation for conducting research on human fighting ability from an evolutionary perspective (e.g., Aung et al, 2021; Lane & Briffa, 2020; Richardson & Gilman, 2019; Třebický et al, 2019). These studies were also the first to draw attention to the use of data from MMA fighters competing in the UFC©.…”
Section: Replicating Zilioli Et Al (2014): Fwhr and Fighting Successmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies laid the foundation for conducting research on human fighting ability from an evolutionary perspective (e.g., Aung et al, 2021; Lane & Briffa, 2020; Richardson & Gilman, 2019; Třebický et al, 2019). These studies were also the first to draw attention to the use of data from MMA fighters competing in the UFC©.…”
Section: Replicating Zilioli Et Al (2014): Fwhr and Fighting Successmentioning
confidence: 99%
“…It should be noted that fight data has been criticised (e.g., Richardson, 2020), as the winner of a single fight can be suddenly and unexpectedly determined which might make dichotomous fight outcome measures (i.e., win/lose) less than preferable. Indeed, much of human contest competition research has used fighter data (Aung et al, 2021; Richardson & Gilman, 2019; Richardson, 2020; Třebický et al, 2013, 2015, 2019). In Study 3, we sought to expand Zilioli et al (2014) by examining the associations between fWHR and contest data among individual fighters.…”
Section: Study 2: Manual Fwhr Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…A classical monogenic explanation for a balanced polymorphism is heterozygote advantage with the best known example being sickle cell anaemia, where affected homozygotes have a high mortality, but heterozygotes, carrying just one copy of the gene, are protected against malaria, which means the gene continues to survive in the population [137]. An alternative mechanism is frequency-dependent selection, where rarer phenotypes have an advantage precisely because of their scarcity, a mechanism found in the lateralisation of scale-eating cichlid fish [392], and often invoked for left-handers being better at fighting or sport [393,394], although there is controversy over the strength of the effects [394][395][396]. The only other major method of polymorphisms being maintained in the population is by mutation, and it is clear that new mutations are responsible for maintaining the relatively rare disease, haemophilia [397].…”
Section: Selection and Evolutionmentioning
confidence: 99%
“…Furthermore, recent studies have found that left-and mixed-handers report being more aggressive and engaging in more fights than right-handers (van der Feen et al, 2020;Zickert et al, 2018). The 'Fighting Hypothesis' of left-handedness proposes that left-handedness has been maintained in humans by natural selection due to left-handers having an advantage in ritual fighting and war (Raymond et al, 1996;Richardson & Gilman, 2019). Left-handers' increased fighting success is thought to be due to their rarity giving them a negative frequency dependent advantage.…”
Section: Introductionmentioning
confidence: 99%